2016
DOI: 10.1002/ase.1610
|View full text |Cite
|
Sign up to set email alerts
|

Social media and anatomy education: Using twitter to enhance the student learning experience in anatomy

Abstract: Neuroanatomy is a difficult subject in medical education, with students often feeling worried and anxious before they have even started, potentially decreasing their engagement with the subject. At the University of Southampton, we incorporated the use of Twitter as a way of supporting students' learning on a neuroanatomy module to evaluate how it impacted upon their engagement and learning experience. The #nlm2soton hashtag was created and displayed (via a widget) on the university's virtual learning environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
155
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 49 publications
3
155
1
4
Order By: Relevance
“…The speed of feedback was also noted by Hennessy et al (2016) to be a strength of social media and in particular Twitter. Several students reported that it helped over the revision period as feedback was rapid and concise due to the 140-character limit.…”
Section: Community and Interactivitymentioning
confidence: 89%
See 3 more Smart Citations
“…The speed of feedback was also noted by Hennessy et al (2016) to be a strength of social media and in particular Twitter. Several students reported that it helped over the revision period as feedback was rapid and concise due to the 140-character limit.…”
Section: Community and Interactivitymentioning
confidence: 89%
“…Webb et al (2015) concluded that Twitter is not a replacement for existing aspects of medical education but that it should be considered as a useful adjunct to the curriculum as students found it added to their education. There were however questions raised over its utility given that each Tweet can only be 140 characters long (Hennessy et al, 2016). Moreover, there remains some concern that this short style of communication will encourage poor writing habits and grammar among students (Grosseck and Holotescu, 2008).…”
Section: Facebookmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the online social media analytical program CREATION Pinpoint, original tweet creation was tracked using the hashtag phrase #colorectalsurgery and the number of tweets that were 'retweets'. Retweets are [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] 21-80 81-300 301-6369 1-4 0 mentions akin to direct quotations of other users' tweets, and so retweeting is a near-instantaneous method of digitally broadcasting and/or disseminating the content of another user; this directly widens the scope of the audience. Data relating to the number of 'impressions' (views) of all tweets, and the number of users who had used the hashtag at least once, were also extracted.…”
Section: Discussionmentioning
confidence: 99%